Capabilities of a Periodic Containerised Railfreight System in Germany - Saenger, Kilian J.; Simon, Timo; Heinitz, Florian (Promet - Traffic&Transportation, 2021)
Based on an analysis of the developments to date, this article originates from and then substantiates long-discussed approaches of a fast, periodic unaccompanied combined rail freight transport network for Germany that corresponds to the target modal split. A four-stage scenario of a market entry is developed. The presented solution incorporates potentially novel aspects such as a network design based on the Deutschlandtakt Cargo integrated periodic timetable framework, the prospective quantity structures as of 2030, and a segmentation for a route-specific mix of two major shipping container types. The set of assessment indicators derived by the model allows to gain insights on the achievable capacities and service levels versus the addressable freight transport demand as well as consequential cost/benefit functions.